Implementasi Sistem Informasi Manajemen untuk Optimalisasi Proses Bisnis di UMKM - Vira Sasmita; Muhammad Irwan Padli Nasution (Yayasan Al-Afif, 2025)
The rapid development of information technology has significantly transformed how Micro, Small, and Medium Enterprises (MSMEs) manage their operations. This study aims to analyze the implementation of Management Information Systems (MIS) as a means to optimize business processes within the MSME sector. The research employs a descriptive qualitative method through literature review and observation of several MSMEs that have adopted digital information systems. The findings indicate that MIS implementation enhances operational efficiency through process automation, improved data accessibility, and increased information accuracy in decision-making. Moreover, MIS contributes to faster customer service and strengthens data-driven marketing strategies. However, the main challenges faced by MSMEs include limited technological competence among human resources and relatively high implementation costs. Therefore, government and institutional support is essential to encourage broader and more sustainable adoption of MIS within the MSME sector.